Association between LRRK2 gene polymorphisms and Parkinson’s disease progression in a Chinese Han population - Zhang, Zhaoting; Geng, Lei; Gao, Jiuxin; She, Ruifang; Ge, Zhonglin; Liu, Jianhua; He, Qianqian; Fu, Bing; Liu, Weiguo (Frontiers in Genetics, 2025)
ObjectiveThe objective of this study was to investigate the association between LRRK2 gene polymorphisms and Parkinson’s disease (PD) risk, as well as the progression of PD, in a Chinese Han population.MethodsA case-control study was carried out on 180 PD patients and 196 healthy controls between October 2019 and October 2023. The demographic and clinical data of all participants were collected. At the baseline and 3-year follow-up, assessment of motor and non-motor symptoms of PD patients were carried out using scales including Unified Parkinson’s Disease Rating Scale parts II, III, and IV, Hoehn and Yahr (H-Y) staging scale, Hamilton Depression Rating Scale, Hamilton Anxiety Rating Scale, Non-motor Symptom Questionnaire, Parkinson’s disease sleep scale, Montreal Cognitive Assessment, and Mini-Mental State Examination. Six single nucleotide polymorphisms (SNPs) of the LRRK2 gene rs1994090, rs2046932, rs2708453, rs34778348, rs4768212, and rs7304279 were selected and genotyped using the MassARRAY platform in all participants.ResultsA strong linkage disequilibrium was observed among the five SNP loci of the LRRK2 gene, including rs1994090, rs2046932, rs2708453, rs4768212, and rs7304279. LRRK2 rs7304279 (OR = 3.572, P < 0.001) and rs34778348 (OR = 0.408, P = 0.003) contributed to the risk of PD development. Carriage of more risk variants were associated with higher risk of PD (OR = 6.467, P < 0.001). Cox proportional hazards model analysis showed that LRRK2 rs7304279 polymorphism was significantly associated with H-Y stage progression (P = 0.030).ConclusionOur findings suggest that LRRK2 rs34778348 and rs7304279 polymorphisms are associated with the risk of developing PD. And LRRK2 rs7304279 polymorphism is correlated with disease progression in PD patients.